A journey of learning organization in social science: interview with Silvia Gherardi. Issue 5 (12th August 2020) - Cuel, Roberta
Abstract : Purpose: This paper aims to attempt to provide an overview of the valuable scientific contribution on learning organization in social science from the perspectives of Professor Silvia Gherardi and discusses the evolution of Silvia's work over her long career. Design/methodology/approach: With the collaboration of this leading scholar, Professor Silvia Gherardi, this paper investigates several topics pertaining to the debate on Learning Organization and provides a unique perspective on the development of these theories. Findings: Starting from the Italian perspective, in which knowledge and learning are mainly social and cultural phenomena, the paper focuses on Professor Silvia Gherardi's contribution to the emerging area of practice-based theorizing of knowing and learning in organizations. Originality/value: In the light of different epistemological approaches and views, the discussion with Professor Silvia Gherardi reveals her practice-based perspective. She proposes a historical analysis of the evolution of the Learning Organization debate, thus providing fertile ground for both researchers and practitioners.